Smart Vest / Muhammad Fayyadh Ahmad … [et al.] - Ahmad, Muhammad Fayyadh; Ab Hamid, Muhammad Khairul Razi; Ahmad Nazeri, Roosyidah; Halmi, Nurin Syafiqah; Muhd Nafi'e Tan, Aqilah; Abdul Razak, Nur Ellyana Nadia (Faculty of Business and Management, 2020)
In the new era people always innovate to make things easier in life and make our daily life run smoothly. Huggle Snug is a company that offers one of the innovations to solve a problem that involves controlling kids. We play a role to create extra hands for a job that needs them to communicate and interact with a kid. Such as pediatric, kindergarten teachers and many more. We create a solution based on the concept of attention. Our product involves many toys and colors to get attention from the kids and attract them, so they are going to forget about the real situation. They are two most important departments in the company that is marketing and production. As a new product in the market, we must make sure our marketing method is suitable and reach our target market because the introductory part is always the difficult one. Beside that our production team is always a priority in making sure our quality of product is always in excellent condition. We are in Melaka, the historical state in Malaysia. The reason we choose Melaka is because that was one of the states that is rapidly growing. Beside that our partnership like Jakel and toys factory is in Melaka. We trust that located near with our resources will make our production run smoothly. The product that we produce will help people around us communicate well with a kid. We also want to create a smile on the kids face, so they would not be afraid of their surroundings especially when they visit a clinic. Because our company trusts that with creating a good surrounding we are creating a better world to make a better generation. So, we always hold that principle when we go to work when we do the work and when we deliver the product.